Ashes to outcasts: cremation, jewish law, and identity in early twentieth-century Germany - Ferziger, Adam S. (AJS review, 2012)
When Chief Rabbi Ḥayim (Vittorio) Castiglioni of Rome (b. 1840) passed away in 1911, he was cremated as per his request and his ashes were then buried in the Jewish cemetery of his native Trieste. One local Jewish newspaper pointed out that Castiglioni's position—cremation is permitted according to Jewish law and is even preferable to traditional burial—was definitely a minority one within the Italian rabbinate. By no means, however, was he accused by any of his rabbinic colleagues of being a heretic.